Elucidating the Consequences of Heparan Sulfate Binding by Heparanase 2 - Gross-Cohen, Miriam; Feld, Sari; Arvatz, Gil; Ilan, Neta; Vlodavsky, Israel (Frontiers in Oncology, 2021)
Unlike the intense research effort devoted to exploring the significance of heparanase in human diseases, very little attention was given to its close homolog, heparanase 2 (Hpa2). The emerging role of Hpa2 in a rare autosomal recessive congenital disease called urofacial syndrome (UFS), clearly indicates that Hpa2 is not a pseudogene but rather a gene coding for an important protein. Hpa2 lacks the heparan sulfate (HS)-degrading activity typical of heparanase, yet exhibits high affinity to HS, affinity that is 10-fold higher than that of heparanase. The consequences of this high-affinity interaction of Hpa2 with plasma membrane HSPG has not been explored yet. Here, we used highly purified Hpa2 protein to examine this aspect. We provide evidence that cells adhere to and spread on dishes coated with Hpa2. We also show that cell migration is attenuated markedly by exogenous addition of Hpa2 to primary and transformed cells, a function that agrees with the anti-cancer properties of Hpa2. Interestingly, we found that exogenous addition of Hpa2 also disrupts the morphology of cell colonies, resulting in cell scattering. This implies that under certain conditions and experimental settings, Hpa2 may exhibit pro-tumorigenic properties. We further developed a panel of anti-Hpa2 monoclonal antibodies (mAb) and show that these properties of Hpa2 are prevented by some of the newly-developed mAb, thus providing new molecular tools to better appreciate the significance of Hpa2 in health and disease.